Pentingnya Pengetahuan Pengelolaan dan Fungsi Manajamen UKS Untuk Kondisi Darurat Siswa di SMA Bawakaraeng - La Ode Nuh Salam; Rusli Abdullah; Erna Kasim; Maharani Maharani; Asfianti Asfianti (ASPIRASI : Publikasi Hasil Pengabdian dan Kegiatan Masyarakat, 2023)
Accidents and emergency conditions can occur anywhere, at any time and attack anyone, including at school. Mistakes or delays in initial treatment can result in a further worsening of the victim's condition which can result in disability or other complications, so it is necessary to pay attention to management and management functions, namely aspects of implementation/movement or action as an effort to optimize and foster UKS. However, the problem is that the knowledge of teachers and school principals is still lacking, there is a lack of funds, and the infrastructure is inadequate for implementing UKS. The aim of this activity is to increase the knowledge of UKS officers and make them truly ready to handle emergency conditions in the school environment and its surroundings. In implementing the provision of UKS services at Bawakaraeng High School, UKS collaborates with teachers. With implementation methods, namely preparation, implementation and evaluation. The results of this activity show that the service activity process went smoothly and there was an increase in knowledge with a pre-test score in the good knowledge category, namely 10 people (33.33%) and less than 20 people (66.67%), then the post test results with good knowledge, namely 28 people (93.33%) and less than 2 people (6.67%)